The Function of Isim Fa'il as Fi'il in the Perspective of the Qur'an - Halim, Abdul (Budapest International Research and Critics University, 2021)
The attitude ofthe clergy grammar and commentators who have given their opinion on the forms associated with isim fa`il, so that it can take the most powerful of their opinions were used as arguments in the case of charitable isim fa`il like fi` il mudhari. Isim fa`il that muta`addi not returned to its fi`il musytaq. Muta`addi his isim fa`il bina` he returned to the meaning or the structure containing musytaq of fi`il muta`addi. Isim fa`il in Arabic tend to the idhafah on grammatical level to bring liveliness isim on cargo construction in accordance with what is indicated by the nature of tsubut fa`il (actor) with regard to the times suggested by suitability relationship.